Interlaboratory study assessing the analysis of supercapacitor electrochemistry data - Gittins J.W.; Chen Y.; Arnold S.; Augustyn V.; Balducci A.; Brousse T.; Frackowiak E.; Gómez-Romero P.; Kanwade A.; Köps L.; Jha P.K.; Lyu D.; et al. (Elsevier B.V., 2025)
Supercapacitors are fast-charging energy storage devices of great importance for developing robust and climatefriendly energy infrastructures for the future. Research in this field has seen rapid growth in recent years, therefore consistent reporting practices must be implemented to enable reliable comparison of device performance. Although several studies have highlighted the best practices for analysing and reporting data from such energy storage devices, there is yet to be an empirical study investigating whether researchers in the field are correctly implementing these recommendations, and which assesses the variation in reporting between different laboratories. Here we address this deficit by carrying out the first interlaboratory study of the analysis of supercapacitor electrochemistry data. We find that the use of incorrect formulae and researchers having different interpretations of key terminologies are major causes of variability in data reporting. Furthermore we highlight the more significant variation in reported results for electrochemical profiles showing non-ideal capacitive behaviour. From the insights gained through this study, we make additional recommendations to the community to help ensure consistent reporting of performance metrics moving forward.